Identifying SUM projections to claustrum is about knowing your limits. Issue 1 (1st January 2019) - Qadir, Houman; Mathur, Brian N.
ABSTRACT: Barbier and colleagues confirm a projection from the supramammillary nucleus to the claustrum using immunohistochemistry to validate the structural boundaries of the claustrum. This refines earlier conclusions made by Vertes and colleagues and highlights the importance of properly anatomically characterizing the claustrum for future structural and functional studies.